Aligning CEO Compensation. Issue 138 (March 2015) - Stringham, Richard
Abstract : Getting CEO compensation right is a perennial source of board concern. Richard Stringham has been exploring CEO compensation approaches and issues and recently attended a webinar 1 on the topic. Here, he reviews his learning through his lens as a consultant to boards implementing the Policy Governance system.